Magnetic Resonance Imaging of synovitis in knees of patients with osteoarthritis without injected contrast agents using T1 quantification. Issue 4 (November 2018) - Burnett, C.; Wright, P.; Keenan, A.-M.; Redmond, A.; Ridgway, J.
Abstract: Introduction: To measure the range of T1 values of synovitis using three Tesla (3 T) magnetic resonance imaging (MRI) in patients with osteoarthritis to assess the potential of T1 mapping for identifying synovitis from other features in the knee on unenhanced magnetic resonance scans. Methods: After receiving institutional ethical approval, 83 patients who met the American College of Rheumatology criteria for diagnosis of osteoarthritis of the knee were scanned using a 3 T Magnetic Resonance Imaging scanner. T1 maps were calculated from spoiled gradient echo images acquired with five different flip angles of 5°–25°. Mean values for the T1 measurements were calculated and compared to existing data from the published literature for anatomical and pathological structures of the knee. Results: T1 values recorded in patients suffering from osteoarthritis demonstrated that T1 values for synovitis (confirmed on gadolinium enhanced images) fall in a narrow range (849–1277 ms, mean 1005 ms SD 91) delineating this from other structures of the knee such as muscle (T1 value range 1305–2638 ms, mean 1785 ms SD 304) and synovial fluid (T1 value range 3867–4129 ms, mean 3915 SD 899) at 3 T. Conclusion: T1 values measured in synovitis in patients with osteoarthritis of the knee demonstrated a range of values distinct to those measured in muscle and synovial fluid at 3 T. This offers potential for the use of T1 maps to delineate or quantify synovitis in patients who are unwilling or unable to receive injectable contrast agents. Highlights: The mean T1 value of synovitis at 3 T in patients with OA of the knee is 1005 ms ± 91. T1 mapping of synovitis can be used to demonstrate synovitis without gadolinium. An inversion recovery sequence can use the calculated T1 time to image synovitis.